Pheno-morphological traits of diverse Brassica juncea (L.) genotypes determining variability in Lipaphis erysimi (Kaltenbach) population build-up - Ipsita Samal,; Naveen Singh,; Tanmaya K. Bhoi,; Mukesh K Dhillon, (Journal of Oilseed Brassica, 2026)
Role of Brassica juncea pheno-morphological variation in imparting resistance to Lipaphis erysimi was studied. Therewas significant variation for most phenotypic and yield attributing traits, and aphid resistance indices on the testgenotypes, across seasons, and for genotype × season interactions. Genotype RBJ 49 with longer siliquae, greaternumber of siliquae and seeds per siliqua was found with moderate aphid resistance. Taller genotypes PDZ 6 and RBJ 11with small siliquae although took longer time to flower and mature, aphid resistance indices were lower than on othergenotypes. Genotype IC 355399 having bunchy inflorescence, dark yellow flowers and higher siliquae, harbouredgreater aphids, while GP 454 and RP 11-2-1-3-1 having cream colour petals displayed opposite reaction towards aphids.In spite of significant variability in test genotypes for seedling colour, petal colour and siliquae orientation, theirregression coefficients were nonsignificant with number of aphids and aphid resistance indices. However, path coefficientanalysis revealed that number of aphids, aphid population and damage indices, point to first branch and siliqua, seedsper siliqua, total siliquae and siliquae length have significant association with aphid resistance index, indicating thatthese traits directly or indirectly contribute to differential reaction against L. erysimi in B. juncea.